KINERJA PENGELOLAAN EKOWISATA DI KAWASAN LERENG SELATAN TAMAN NASIONAL GUNUNG MERAPI DENGAN PENDEKATAN INSTITUTIONAL DEVELOPMENT FRAMEWORK (IDF) - , Yudy Sunantri ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Community-based tourism development is to improve the welfare and prosperity of the people which canât be separated from the economic dimension in tourism development activities which could be the leading sectors and is able to encourage economic activity through ecotourism. The management plan attempted to accommodate a variety of development opportunities. Thus, in the preparation and drafting of management plans, an effort involving community participation is a prerequisite for effective and efficient management plan drawn up. In general, the methods used in this research is descriptive qualitative method with analysis based on qualitative and quantitative data. Qualitative method is defined as a procedure of research that produces descriptive data in the form of words written or spoken of people or behaviors that can be observed (Bagdan and Taylor in moloeng, 2002, p3). The method used in this study is the IDF (Institutional Development Framework) The result of this research showed that the level of institutional development of Mount Merapi National Park ecotourism management organization at the stage of developments and continuous efforts are needed to get to the stage of stabilization and maturity and still struggle in an effort to improve performance effectiveness to achieve effectively and higher levels of development. Factors relating to institutional, policy, legislation and regulations on the management of ecotourism where the readiness of an organization that is National Park Office which is still classified as a Technical Management Unit that was young and continues to struggle to get to the stage of National Park Office performance development. Orientation in this management of ecotourism is of community-based tourism.